Contribution of Low Enthalpy Geothermal Energy in the Retrofit of a Single-Family House: A Comparison between Two Technologies - Diana D’Agostino; Francesco Minichiello; Angela Valentino (Journal of Advanced Thermal Science Research, 2020)
In recent years, the European Union has developed a sustainable, competitive, safe, and “decarbonised” energy approach. To achieve this objective, especially in highly urbanized contexts, there is a need to drastically improve the energy behavior of buildings and related energy systems. For this purpose, the aim of this paper is to analyse two very promising technologies that exploit the geothermal energy of the ground: the Earth-to-Air Heat eXchanger (EAHX) and the Ground Source Heat Pump (GSHP). These two systems are used as an energy retrofit strategy for the air conditioning system in an existing single-family house, located in Naples (south Italy). The building and the related systems are dynamically simulated using the DesignBuilder software. The results show energy savings of these two systems (compared to a traditional solution with an air-to-water heat pump) between 13% and 28%, with a total yearly primary energy consumption of about 80 kWh/m2 for the case with EAHX and around 67 kWh/m2 for the case with GSHP.